2021
DOI: 10.31314/ajamiy.10.2.308-325.2021
|View full text |Cite
|
Sign up to set email alerts
|

Pola Kata Jama’ Taksīr Dalam Novel “Qātilu Hamzah” Karya Najib Kailani (Analisis Morfosintaksis

Abstract: This study aims to describe the word patterns of jama 'takṡīr, grammatical signs, and their function and position in the novel "Qātilu Hamzah" by Najib Kailani morphosyntactic theory. The data collection technique in this study used a descriptive qualitative method with the note-taking method. Meanwhile, the data analysis used descriptive morphosyntactic analysis. Based on the results of the analysis, the following findings were found. First, the pattern of jama 'takṡīr in the novel "Qātilu Hamzah" by Najib Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…It can be found in the book series of counseling in writing sentences in Indonesia (Sasangka, 2014). Agustina et al, (2021) also identified the pattern of jama' taksîr in Najib Kailan's novel "Qâtilu Hamzah".…”
Section: Arabiyâtmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found in the book series of counseling in writing sentences in Indonesia (Sasangka, 2014). Agustina et al, (2021) also identified the pattern of jama' taksîr in Najib Kailan's novel "Qâtilu Hamzah".…”
Section: Arabiyâtmentioning
confidence: 99%
“…The irregular plural form in Arabic, known as jam'u taksîr , presents a significant problem in language learning. In addition to its many divisions, the formation standard is different and there are no fixed rules (Agustina et al, 2021). Mardiyah et.…”
Section: Introductionmentioning
confidence: 99%
“…Cherif et al, melakukan penelitian tentang text mining menggunakan data yang cukup besar dengan membangun rule sintaks berbasis stemmer untuk meningkatkan efektivitas dalam pencarian kata pada bahasa arab [17]. Penelitian [18] tentang analisis novel yang berjudul "Qātilu Hamzah" untuk mencari wazan atau pola dan jenis-jenis jama' takṡīr berdasarkan wazan, jenis jama' takṡīr , dan juga tanda-tanda gramatikal jama' takṡīr, dengan sistem manual dan analisis dihasilkan dari 61 data, peneliti mengklasifikasikan sesuai dengan pola derivasinya serta fungsi dan kedudukan terhadap data yang ditemukan sesuai dengan pola wazn (bentuk) jama' takṡīr. Penelitian tentang "kata penting" telah dilakukan dengan Inferensi menggunakan Bidirectional LSTM model dan Inner-Attention [19].…”
Section: Pendahuluanunclassified
“…Struktur bahasa arab mengenal Subjek (Laki-laki, perempuan, dan Jamak), serta dikategorikan berdasarkan Madhi, Mudhari dan Amr. Pola dasar tersebut mengalami perubahan yaitu [18]…”
Section: Wazanunclassified